Visagismo no ambiente virtual: uma análise do design digital de aplicativos de beleza e estética - Antunes, Fabio Ritter (2020)
This research aims to investigate the construction of personal image in the collective virtual world and its evolution from the resources of facial visagism. What justifies this investigation is the lack of debate on the proposed theme, from the perspective of visagism, still little explored and lacking scientific research compared to other academic areas, especially in Brazil. What motivates the accomplishment of this research is the possibility of investigating alternatives that can contribute to the image adequacy, from a project in the collective virtual environment based on the facial visagism. This research seeks to answer the following problematic question: How can visagism resources contribute to the evolution of collective digital imagery design? It is hypothesized that visagism from digital technologies can contribute to the improvement of the virtual imagery project. We opted for the descriptive qualitative scientific research methodology, with bibliographic / documentary data origin, since it faces theoretical and empirical aspects, in order to fulfill its general objective. The review of previous studies related to the proposed theme focused on the period from 2000 to 2019, including books, scientific articles, theses and dissertations, considering research available in the following online databases: a) PUC-SP (Pontifical) Thesis and Dissertation Bank Catholic University of São Paulo), b) Capes Thesis and Dissertation Bank, c) Google Scholar. Also considered for the review of previous studies, the articles available in the Scientific Electronic Library Online - SciELO. The theoretical references that support this research are the concepts of visagism (HALLAWELL, 2010), and digital image (MCGONIGAL, 2012; SCHELL, 2011; SANTAELLA, 1993). The context of this investigation involves spaces for research, teaching and extension of the institutions where partner researchers work. The expected results with this research are: creation of a new facial visagism application with the inclusion differential of the emotional state expressed in the face